2013
DOI: 10.1002/jps.23667
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Nanoemulsion Formulation Strategy for Oral Bioavailability Enhancement of Danazol in Rats and Dogs

Abstract: The objective of this study was to determine whether nanoemulsion formulations constitute a viable strategy to improve the oral bioavailability of danazol, a compound whose poor aqueous solubility limits its oral bioavailability. Danazol-containing oil-in-water nanoemulsions (NE) with and without co-surfactants stearylamine (SA) and deoxycholic acid (DCA) were prepared and characterized. Nanoemulsion droplets size ranging from 238 to 344 nm and with surface charges of −24.8 mV (NE), −26.5 mV (NE-DCA), and +27.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 35 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…Given the insolubility of lipids in water, the antibacterial activity of oil could be improved through the production of emulsions. Indeed, many studies showed the effectiveness of nanoemulsions to increase the bioavailability of hydrophobic active substances [ 11 ]. Furthermore, oil could be obtained by different extraction methods among which are enzymatic extraction, chemical extraction, and physical extraction.…”
Section: Introductionmentioning
confidence: 99%
“…Given the insolubility of lipids in water, the antibacterial activity of oil could be improved through the production of emulsions. Indeed, many studies showed the effectiveness of nanoemulsions to increase the bioavailability of hydrophobic active substances [ 11 ]. Furthermore, oil could be obtained by different extraction methods among which are enzymatic extraction, chemical extraction, and physical extraction.…”
Section: Introductionmentioning
confidence: 99%
“…In the second section of this study, we introduce a model nonelectrolyte PWSD, danazol (Figure ), to the system to observe the distribution of the drug within the lipid phase. Danazol has a logP of 3.9 and aqueous solubility of 0.58 μg/mL and has been extensively studied as a representative PWSD. This is the first study of quaternary phase behavior using a model system of digested lipid, digested triglyceride, bile salt, and water using both experimental and MD techniques.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the kinetics of four NE formulations were compared. The mean NE diameters tended to increase with the increase in PEG molecular weight, confirming PEG’s brush-like conformation, whereas a mushroom-like conformation would result in a decrease in NE diameter [ 51 , 52 , 53 , 54 ]. Dynamic MRI is a powerful tool to rapidly follow, in a longitudinal manner, the stealth properties of nanocarriers over time, in contrast to classical methodologies that rely on blood sampling at defined time points.…”
Section: Discussionmentioning
confidence: 98%
“…To our knowledge, only a few studies have investigated how to prolong the half-life of PEGylated NEs [ 30 , 51 , 52 ]. Cheng et al studied how different molecular weights and different concentrations of lipid–PEG affected NE size but did not analyze their pharmacokinetic profiles [ 52 ].…”
Section: Discussionmentioning
confidence: 99%